2008
DOI: 10.1345/aph.1l130
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Adverse Drug Reaction Electronic Reporting System Integrated into a Hospital Information System

Abstract: An ADR reporting system integrated into the electronic hospital information system is effective for increasing the number of ADRs reported to the national drug surveillance system. Allowing nurses to report ADRs in a manner similar to that of physicians and pharmacists, as well as automatic entry of certain data into the form, contributes to the improvement of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 9 publications
1
26
1
1
Order By: Relevance
“…Worldwide, many systems use electronic health records to facilitate adverse event reporting, with the same goal as our work, which is to not overload healthcare professionals with additional administrative work to report ADR [7,13,14] . These systems can be included in the EHR and be easily completed [13] or can actively help in form filling with the automatic input of certain information already included in the EHR [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, many systems use electronic health records to facilitate adverse event reporting, with the same goal as our work, which is to not overload healthcare professionals with additional administrative work to report ADR [7,13,14] . These systems can be included in the EHR and be easily completed [13] or can actively help in form filling with the automatic input of certain information already included in the EHR [7].…”
Section: Discussionmentioning
confidence: 99%
“…These systems can be included in the EHR and be easily completed [13] or can actively help in form filling with the automatic input of certain information already included in the EHR [7]. During the ALIAS (Albumin in Acute Stroke Trial) experience, authors decided to integrate an electronic safety reporting module into the existing web-based system to deal with safety reporting obligations of a multicentre clinical trial [15].…”
Section: Discussionmentioning
confidence: 99%
“…The continuous development of electronic data collection and the introduction of electronic patient records are a unique opportunity to facilitate these developments. [20] Unfortunately, because of resource limitations, there has not yet been any widespread implementation in general practice. Overall, active pharmacovigilance poses an important feature in the pharmacovigilance process, which, particularly in the pediatric population, should be utilized more and replace the simple standard of spontaneous reporting.…”
Section: Detection Of New Adrsmentioning
confidence: 99%
“…1 Many institutes have been struggling with underreporting and poor interdisciplinary involvement in ADEs. 2 However, studies have shown that the number of ADE reports can be increased by at least 50% over a 6-month period by introduction of the electronic reporting system.…”
Section: Introductionmentioning
confidence: 99%
“…2 It should be noted that all health care professionals provide pivotal information on managing ADEs, 3 and enabling nurses to report electronically has been proven to increase ADE reports from 4.41 to 6.5 per month. 1 Establishing an efficient electronic system can further advance the interdisciplinary participation. A well-designed electronic system easily accessible by all appropriate health care professionals is crucial in enabling efficient interdisciplinary communication and managing ADEs.…”
Section: Introductionmentioning
confidence: 99%